Synchronous renal cell carcinoma and multiple myeloma: report of two cases and review of the literature - (:unkn) unknown (ZERBINIS MEDICAL PUBL, 2009)
Coexistence of renal cell carcinoma (RCC) and multiple myeloma (MM) is an extremely rare condition. Appearance of synchronous RCC and MM was not reported independently so far In this brief communication, we report 2 cases of synchronous RCC and MM, discuss common risk factors or pathogenetic mechanisms seen in either RCC or MM, point out the importance of IL-6 in this coexistence and provide some descriptive properties of all reported synchronous RCC and MM cases.
Keywords: diagnosis; multiple myeloma; multiple primary neoplasms; renal cell carcinoma; second primary neoplasms; MALIGNANCIES; INTERLEUKIN-6; ASSOCIATION